The Sermons, Manuscripts, and Language of Roberto Caracciolo da Lecce
1 online resource (256 pages)
Keywords: The book offers studies on different aspects of the life, activity, and written works of Roberto da Lecce, one of the most famous preachers of fifteenth-century Italy. His preaching cycles in Italian cities were attended by huge crowds and are representative for the activity of many other less-known confreres and, in the meantime, exceptional for their number and success. His sermons were read and re-used throughout Europe, contributing to shaping the shared religious culture. The nine authors of this book have addressed this polyhedric figure from ten different perspectives. Contributors are Yoko Kimura, Salvatore Leaci, Andrea Radošević, Cecilia Rado, Carolyn Muessig, Giacomo Mariani, Marco Maggiore, Lyn Blanchfield, and Steven J McMichael.